2013
DOI: 10.1155/2013/948258
|View full text |Cite
|
Sign up to set email alerts
|

Use ofFrankiaand Actinorhizal Plants for Degraded Lands Reclamation

Abstract: Degraded lands are defined by soils that have lost primary productivity due to abiotic or biotic stresses. Among the abiotic stresses, drought, salinity, and heavy metals are the main threats in tropical areas. These stresses affect plant growth and reduce their productivity. Nitrogen-fixing plants such as actinorhizal species that are able to grow in poor and disturbed soils are widely planted for the reclamation of such degraded lands. It has been reported that association of soil microbes especially the nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 56 publications
(75 reference statements)
0
48
0
1
Order By: Relevance
“…Like rhizobia–legume symbioses, bacteria are hosted in root nodules and fix atmospheric nitrogen (Perrine-Walker et al, 2011). Some actinorhizal plants such as Casuarinaceae trees are largely used in land reclamation pros including salinized land (reviewed in Diagne et al, 2013). Several studies have therefore reported strategies to improve the tolerance of these plants to salt stress.…”
Section: Strategies To Improve Salt Tolerance In Cropsmentioning
confidence: 99%
“…Like rhizobia–legume symbioses, bacteria are hosted in root nodules and fix atmospheric nitrogen (Perrine-Walker et al, 2011). Some actinorhizal plants such as Casuarinaceae trees are largely used in land reclamation pros including salinized land (reviewed in Diagne et al, 2013). Several studies have therefore reported strategies to improve the tolerance of these plants to salt stress.…”
Section: Strategies To Improve Salt Tolerance In Cropsmentioning
confidence: 99%
“…Under saline environments, Casuarina has proven a greatest potential in N 2 -fixation when inoculated with compatible Frankia strains leading to effective nodule formation and in turn improving Casuarina growth (Reddell et al 1986;Diagne et al 2013). Enhancing Casuarina growth will help improve management practices of soil salinity and improves the sustainable use of irrigated lands.…”
Section: Introductionmentioning
confidence: 99%
“…Frankia forms a perennial root organ called nodule where bacteria are hosted. Two type of nodules formation occur in actinorhizal symbiosis, the intercellular and extracellular infections (Benson and Silvester, 1993;Diagne et al, 2013).…”
Section: Discussionmentioning
confidence: 99%